THE EFFECT OF THE SCHOOL ENVIRONMENT ON CHARACTER FORMING CHILDREN IN CLASS V AT SDN 01 MARISA POHUWATO DISTRICT - Marsella Desriyarini Gui (SEMAR Journal : Educational Studies, 2022)
The problem raised in this study is the school environment which is a forum or place for students who are guided from all knowledge, morals, skills, aspects which are very important things to be fostered in the school environment, so that not only knowledge is prioritized. But especially to the formation of character and also the inculcation of moral values to students who are different in the school environment and of course it cannot be separated from the role of educators who are in the school environment.  This type of research is descriptive qualitative research. This research was conducted on fifth grade students as a sample of 2 informants who were considered to have knowledge and information about the problems studied, namely the Effect of School Environment on Children's Character Building at SDN 01 Marisa, Marisa District, Pohuwato Regency. Data collection uses instruments in the form of; Observations and interviews, as well as in-depth documentation of information. The data were analyzed qualitatively.  By conducting this research, it showed good results in the Research on the Effect of the School Environment on Children's Character Building by interviewing informants who were seen from the aspect of the influence of educators, students, classrooms, playing fields, canteens, while students and educators both had positive influence and also negative influence on the formation of the character of students.